DESAIN LINER INJEKSI PADA RESERVOIR PANAS BUMI YANG DIDOMINASI UAP DENGAN TEMPERATUR 285 ? - Theodore Halomoan, Gabriel
A geothermal injection well's casing as well as liner is among the well integrity elements. Internal loads including wellbore condition (e.g., dogleg severity/DLS, lost circulation) or even external loads such as facies and effect from neighboring wells exert pressure on casing/liner (production and injection). Internal and external loads interact and must be projected accurately, repeatedly, and consistently for casing/liner design over the life of the well.(Marbun, et al., 2020). In theory, there are numerous load calculation guidelines available, such as those in the New Zealand Standard (NZS 2403:2015). Apparently, this is very usual and cannot be easily implemented to cases in the field, particularly in Indonesia, so it is necessary to improve calculations (Marbun, et al., 2020). The study intends to use the method proposed by Marbun (2020) to evaluate the lower liner in the HX5A geothermal injection well in a steam-dominated geothermal reservoir with temperatures up to 285 ?. The lower injection liner's load is reconstructed and recalculated. The maximum load within every phase of operation is taken into account in the recalculation. According to the results of the recalculation, failure occurs in the lower injection liner. Furthermore, the approach developed in this study was adopted as a standard operating procedure (SOP) for the construction of the next injection well at X Field. (Marbun, et al., 2020).